Legal nature of special proceeding as type of civil proceeding - Aliyeva, L.R. (Bulletin of the Karaganda University “Law Series”, 2018)
The task to examine the major issues of special proceeding institute as type of civil proceeding is set in thepresent article. Modern civil turnover includes the need to establish the existence of legal facts, determining the legal regime of the different private law relations and the establishment of the legal status of their participants in order to implement the rights of these subjects in the sphere of private law. These issues are resolved by the courts of general jurisdiction in a particular order. Civil legislation provides for protection of the legitimate interests of the participants of civil relations, which has not yet been broken, and not contested, but which also needs to be protected from the government because of the uncertainty of specific legal facts, the legal status of citizens, and so on. The special proceeding is existing to protect such interests. The special proceeding is the third type of civil proceeding, which protects the personal rights and interests in cases where such rights and interests are violated, in the event of the need to establish rights which are the basis for the implementation of these rights. In the course of special proceeding eliminate of legal uncertainties and inaccuracies in respect of the circumstances, actions or events, carrying out of the control for the legality of the activities of notaries and RACS, thus preventing legal conflicts may be.